Bordetella adenylate cyclase toxin elicits chromatin remodeling and transcriptional reprogramming that blocks differentiation of monocytes into macrophages - Ahmad, Jawid Nazir; Modrak, Martin; Fajfrova, Marketa; Sotoca, Blanca Martin-Borja; Benada, Oldrich; Sebo, Peter (mBio, 2025)
Bordetella pertussis infects human upper airways and deploys an array of immunosuppressive virulence factors, among which the adenylate cyclase toxin (CyaA) plays a prominent role in disarming host phagocytes. CyaA binds the complement receptor-3 (CR3 aka αMβ2 integrin CD11b/CD18 or Mac-1) of myeloid cells and delivers into their cytosol an adenylyl cyclase enzyme that hijacks cellular signaling through unregulated conversion of cytosolic ATP to cAMP. We found that the action of as little CyaA as 22 pM (4 ng/mL) blocks macrophage colony-stimulating factor (M-CSF)-driven transition of migratory human CD14+ monocytes into macrophages. Global transcriptional profiling (RNAseq) revealed that exposure of monocytes to 22 pM CyaA for 40 hours in culture with 20 ng/mL of M-CSF led to upregulation of genes that exert negative control of monocyte to macrophage differentiation (e.g., SERPINB2, DLL1, and CSNK1E). The sustained CyaA action yielded downregulation of numerous genes involved in processes crucial for host defense, such as myeloid cell differentiation, chemotaxis of inflammatory cells, antigen presentation, phagocytosis, and bactericidal activities. CyaA-elicited signaling also promoted deacetylation and trimethylation of lysines 9 and 27 of histone 3 (H3K9me3 and H3K27me3) and triggered the formation of transcriptionally repressive heterochromatin patches in the nuclei of CyaA-exposed monocytes. These effects were partly reversed by the G9a methyltransferase inhibitor UNC 0631 and by the pleiotropic HDAC inhibitor Trichostatin-A, revealing that CyaA-elicited epigenetic alterations mediate transcriptional reprogramming of monocytes and play a role in CyaA-triggered block of monocyte differentiation into bactericidal macrophage cells.IMPORTANCETo proliferate on host airway mucosa and evade elimination by patrolling sentinel cells, the whooping cough agent Bordetella pertussis produces a potently immunosubversive adenylate cyclase toxin (CyaA) that blocks opsonophagocytic killing of bacteria by phagocytes like neutrophils and macrophages. Indeed, chemotactic migration of CD14+ monocytes to the infection site and their transition into bactericidal macrophages, thus replenishing the exhausted mucosa-patrolling macrophages, represents one of the key mechanisms of innate immune defense to infection. We show that the cAMP signaling action of CyaA already at a very low toxin concentration triggers massive transcriptional reprogramming of monocytes that is accompanied by chromatin remodeling and epigenetic histone modifications, which block the transition of migratory monocytes into bactericidal macrophage cells. This reveals a novel layer of toxin action-mediated hijacking of functional differentiation of innate immune cells for the sake of mucosal pathogen proliferation and transmission to new hosts.
Keywords: macrophages; přeprogramování buněk; faktor stimulující kolonie makrofágů; epigenetics; restrukturace chromatinu; monocyty; signální transdukce; buněčná diferenciace; Signal Transduction; Macrophage Colony-Stimulating Factor; Bordetella pertussis; kultivované buňky; lidé; Humans; cyclic AMP; Monocytes; makrofágy; differentiation; Cells, Cultured; adenylátcyklasový toxin; RTX toxins; Macrophages; Cellular Reprogramming; monocytes; Chromatin Assembly and Disassembly; Adenylate Cyclase Toxin; Cell Differentiation